An Analysis of Language Politeness Adherence and Violations in the YouTube Comment Section of the "Dirty Vote" Video - Azzahra Novira; Zulfitriyani; Wahyudi Rahmat (Jurnal Bebasan, 2024)
This study investigates the forms of adherence to and violations of language politeness principles in the YouTube comment section of the video titled "Dirty Vote." Utilizing a qualitative-descriptive approach, the research aims to reveal how principles of language politeness are both observed and breached in online discourse. The data were collected from comments posted by viewers of the "Dirty Vote" video using several techniques: (1) free listening technique (SBLC) to read and identify relevant comments, (2) a recording technique where comments containing politeness principles were captured via screenshots, and (3) a note-taking technique to organize the data in an inventory table. The data analysis was conducted in three stages: data reduction through matching and distribution methods, data presentation, and conclusion drawing. The study reveals that viewers' comments adhered to several politeness maxims, including the tact, approbation, modesty, agreement, and sympathy maxims. Simultaneously, the study identifies violations of the same maxims, with the addition of the generosity maxim. Notably, adherence to the generosity maxim was not observed in any comments. These findings contribute to a deeper understanding of language politeness in digital interactions, specifically within the context of public discourse on YouTube. This research underscores the dynamic nature of language use in online spaces, where politeness norms are continuously negotiated and reshaped.